Phenotypic Relationships between Body Measurements of Indigenous Chickens in Borno State - Abdulraheem, A.O.; Raji, A. O.; Alade, N. K.; Mohammed, I. D.; Aliyu, J.; Mohammed, G.; Saleh, B.; Adamu, J.; Mohammed, A. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
Phenotypic correlations between morphological characteristics of 600 indigenous chickens (naked neck, normal and frizzled) from the central and southern parts of Borno state were determined. Data on morphometric traits were collected over three seasons in the study area and analyzed. The traits measured were Body weight (BW), Ornithological measurement (OM), wing span (WS), neck length (NL), back length (BL), keel length (KL), tail feather length (TFL), thigh length (THL) and shank length (SL). The mean body weights for normal, frizzled and naked neck chickens were 1481.66, 1250.21 and 1655.73 g, respectively while Cocks and hens had mean BW of 1628.58 and 1248.98 g. Sex and genotype had highly significant (P<0.01) effects on all measurements. Correlation analysis revealed that the highest positive (0.81) correlation was between OM and BL and the lowest (0.00) between KL and NL for naked neck chickens. The highest negative (-0.33) correlation was between TL and KL and lowest (-0.01) between BW and TFL for frizzled. In general, correlation coefficients between morphometric traits were higher for normal feathered and naked neck than frizzled. BW had significant (P<0.05) positive relationships with all body measurements except KL in frizzled (0.13) and naked neck (0.18) which were not significant (P>0.05). Coefficients of correlation were generally higher for chickens in the south than those in central. Similarly, cocks had higher coefficients between morphometric traits than hens. The medium to high relationships between most traits for these birds could mean that selection for improvement of one trait may lead to improvement in the other.